Echocardiographic screening of 4107 Nigerian school children for rheumatic heart disease. Issue 6 (8th April 2019) - Ekure, Ekanem N.; Amadi, Casmir; Sokunbi, Ogochukwu; Kalu, Nnenna; Olusegun‐Joseph, Akinsanya; Kushimo, Oyewole; Hassan, Olayinka; Ikebudu, Desmond; Onyia, Sophia; Onwudiwe, Chinonso; Nwankwo, Victor; Akinwunmi, Remi; et al.
Abstract: Objective: Echocardiographic screening for Rheumatic Heart Disease (RHD) in Africa has revealed prevalence rates in the range of 0.5–7.4%. There are no recent large population‐based studies in Nigeria. The objective of the study was to determine the prevalence of RHD in a large sample of Nigerian school children. Methods: Using portable transthoracic echocardiography and auscultation, school children aged 5 years to 16 years in Lagos, Nigeria were screened for RHD. Diagnosis was based on the 2012 World Heart Federation echocardiographic criteria. Results: The 4107 children screened had mean age of 11.3 years (SD = 2.6) and 2206 (53.7%) were females. There were 38 children with abnormal echocardiograms, of which 11 (0.27%) showed RHD including two cases of definite RHD giving a prevalence of 2.7/1000 [2.9/1000 in the peri‐urban, 2.4/1000 in the urban area). Echocardiography detected RHD 10 times better than auscultation [echocardiography 11 (0.27%) vs . auscultation 1 (0.02%); P = 0.003]. The remaining 27 children with abnormal echocardiograms had congenital heart defects (CHD) giving a prevalence of 6.6/1000 for CHD, a yield higher than for RHD. Conclusion: Prevalence of RHD among school children in Lagos, South West Nigeria is low compared to other African countries, possibly due to better access to medical care and antibiotic treatment for infections. Our data provides evidence that RHD prevalence may vary substantially within sub‐Saharan Africa, necessitating targeted population‐based sampling to better understand disease burden and distribution. Further work is needed to compare within‐ and between‐country RHD prevalence as a basis for programme planning and control efforts. Abstract : Objectif: Le dépistage échocardiographique de la cardiopathie rhumatismale (CR) en Afrique a révélé des taux de prévalence compris entre 0, 5 et 7, 4%. Il n'existe pas de grande étude récente de population au Nigéria. L'objectif de l'étude était de déterminer la prévalence de la CR dans un grand échantillon d'écoliers nigérians. Méthodes: A l'aide d'une échocardiographie et d'une auscultation trans‐thoraciques portables, des écoliers âgés de 5 à 16 ans de Lagos, au Nigeria, ont été soumis à un dépistage de la CR. Le diagnostic reposait sur les critères échocardiographiques de la Fédération Mondiale du Cœur de 2012. Résultats: Les 4.107 enfants testés avaient un âge moyen de 11, 3 ans (DS = 2, 6) et 2.206 (53, 7%) étaient de sexe féminin. Il y avait des échocardiogrammes anormaux chez 38 enfants, dont 11 (0, 27%) présentaient une CR, y compris deux cas de CR bien définie, donnant une prévalence de 2, 7/1000 [2, 9/1000 dans les zones périurbaines, 2, 4/1000 dans les zones urbaines). L'échocardiographie a détecté une CR 10 fois mieux que l'auscultation [échocardiographie 11 (0, 27%) contre auscultation 1 (0, 02%); p = 0, 003]. Les 27 enfants restants dont les échocardiogrammes étaient anormaux avaient une cardiopathie congénitale (CHD), ce qui donnait une prévalence de 6, 6/1.000 pour les cardiopathies congénitales, donnant une prévalence de 6, 6/1000, un rendement supérieur à celui de la CR. Conclusion: La prévalence de la CR parmi les écoliers à Lagos, dans le sud‐ouest du Nigéria, est faible comparée à celle d'autres pays africains, probablement en raison d'un meilleur accès aux soins médicaux et au traitement antibiotique contre les infections. Nos données fournissent des preuves que la prévalence de la CR peut varier considérablement en Afrique subsaharienne, nécessitant un échantillonnage ciblé de la population pour mieux comprendre la charge et la répartition de la maladie. Des études supplémentaires sont nécessaires pour comparer la prévalence de la CR intra‐ et inter pays en tant que base des efforts de planification et de lutte des programmes.